A Role of Circulating biomarkers and Maternal-Infant Outcomes after Anticoagulant Therapy In Pregnant Women with Mechanical Heart Valve Replacement: serum TAT, sP-Selectin, NGAL, and PlGF - Shaohui Li, Shaohui Li (Journal of Medical Biochemistry, 2026)
Aim: To investigate the effect of standardized anticoagulation on parturients and fetuses during pregnancy after mechanical heart valve replacement (MHVR) and to evaluate novel serum biomarkers reflecting coagulation activation, endothelial function, placental perfusion, and renal injury.Methods: 100 parturients during pregnancy after MHVR who received treatment in Hebei Xingtai People's Hospital from January 2019 to December 2024 were recruited and divided into low-molecular-weight heparin (LMWH) group (n=50) and regional citrate anticoagulation (RCA) group (n=50). Coagulation parameters (PT, APTT, TT, FIB, PLT), novel biomarkers (thrombin-antithrombin complex [TAT], soluble P-selectin [sP-selectin], D-dimer), renal biomarkers (urea nitrogen, serum creatinine, neutrophil gelatinase-associated lipocalin [NGAL], asymmetric dimethylarginine [ADMA]), placental and inflammatory markers (placental growth factor [PlGF], interleukin-6 [IL-6]) were compared between groups. Maternal complications and abnormal fetal development were observed.Results: PT and APTT of parturients in RCA group markedly surpassed those in LMWH group, TT was notably inferior to that in LMWH group; FIB decreased more and PLT increased more in RCA group; TAT, sP-selectin, and D-dimer levels were significantly lower in RCA group (P
Keywords: serum TAT, sP-Selectin, NGAL, PlGF , mechanical heart valve replacement; parturient; anticoagulant therapy; maternal-infant outcomes; regional citrate anticoagulation; novel serum biomarkers